Thermochemical investigation on a novel sodium-metal-halide battery configuration: Experimental and FEM model results. (October 2019) - D'Urso, C.; Briguglio, N.; Bonanno, A.; Ferraro, M.; Antonucci, V.; Vasta, S.
Highlights: A prototype of a flat cell of a ZEBRA battery has been developed and extensively tested at CNR ITAE. FEM analysis has been carried out using the software COMSOL MULTIPHYSICS to guarantee low thermal losses and optimal warm up time. Development of the chemistry of the cathode by the combination of the two main redox pairs Ni/NiCl2 and Fe/FeCl2 with Fe sulphides, New cell validated considering charge/discharge cycles aimed at determining capacity, duration, efficiency, energy density. The performances in terms of efficiency are: 76% energy efficiency; 84% faradic efficiency Abstract: In this work the development, tests and thermodinamic numerical simulations on a flat cell of an innovative Sodium-metal-halide battery has been presented: a prototype of a single cell was designed, realized and eventually extensively tested at CNR-ITAE. The following performances were recorded during the test stage: 76% energy efficiency and 84% faradic efficiency. Similarly to tubular cells commercially available, the flat cells constituting the battery have to be placed into an insulated box equipped with a proper heating system because of their high working temperatures. To this aim, a numerical thermal analysis by using the software COMSOL MULTIPHYSICS has been carried out to evaluate the best solution to guarantee a reduced thermal loss and reasonable warming up time.